2008
DOI: 10.3164/jcbn.2008064
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects and Insulin Resistance Improvement of Chromium Combined with Vitamin C and E Supplementation for Type 2 Diabetes Mellitus

Abstract: Summary To determine the effects of combined supplementation with chromium (Cr) and vitamins C and E on oxidative stress in type 2 diabetes, adult subjects with HbA1c >8.5%. Subjects (n = 30) in this randomized, double blind, placebo-control study were divided into three groups (placebo, Cr or Cr + C + E) on daily treatment. The Cr group received 1000 μg of Cr (as Cr yeast); the Cr + C + E group received Cr (1000 μg as Cr yeast) together with vitamins C (1000 mg) and E (800 IU); and, a control group received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 42 publications
2
83
0
2
Order By: Relevance
“…DMG can act as a methyl donor (Friesen et al, 2007) similar to betaine and, additionally, has anti-oxidative properties (Hariganesh and Prathiba, 2000). As methyl donation capacity (Jin et al, 2007) and anti-oxidative action (Lai, 2008) are both associated with increased insulin sensitivity, DMG can possibly influence insulin sensitivity. Other studies report that DMG, used as a dietary supplement, reduces blood lactate level and improves athletic performance in men (Tonda and Hart, 1992), horses (Greene et al, 1996) and dogs (Gannon and Kendall, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…DMG can act as a methyl donor (Friesen et al, 2007) similar to betaine and, additionally, has anti-oxidative properties (Hariganesh and Prathiba, 2000). As methyl donation capacity (Jin et al, 2007) and anti-oxidative action (Lai, 2008) are both associated with increased insulin sensitivity, DMG can possibly influence insulin sensitivity. Other studies report that DMG, used as a dietary supplement, reduces blood lactate level and improves athletic performance in men (Tonda and Hart, 1992), horses (Greene et al, 1996) and dogs (Gannon and Kendall, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The mean HbA1c of 8.0% at baseline fell to 6.6%, reaching the treatment goal range by the end of the supplementation period. The Lai trial, 39 conducted in Taiwan, used a chromium dosage of 1000 lg/d from supplemented yeast (it was unclear what form of yeast was used) in a 6-month RCT with an ITT analysis in 10 T2DM patients with a baseline FPG of >8.5 mmol/L and HbA1c levels of >8.5%. The intervention was associated with a drop in HbA1c from 10.2% to 9.5%, which was above the treatment goal.…”
Section: Studies Measuring Hba1cmentioning
confidence: 99%
“…16 Also, Akinosun and Bolajoko 19 in Ibadan reported decrease in serum TAS in type 2 diabetic patients than controls.Similarly, in Brazil, a study by Medina et al 7 revealed lower plasma antioxidant activity in diabetic patients than in healthy individuals Studies revealed that TAS in type 2 DM is low and this could be attributed to low levels of antioxidant vitamins enzymes and other micro-nutrients in the blood Benrebaiet al 17 andLai. 20 The decrease could be as a result of poor glycaemic control probably because of poor compliance rate of the diabetic patients.…”
Section: Discussionmentioning
confidence: 99%